Pengaruh Keputusan Karier terhadap Psychological Well-Being Remaja: Keterlibatan Orang Tua sebagai Variabel Moderasi - Habib Nahdia Ulwa; Kus Hendar; Meita Sari (Journal of Society Counseling, 2026)
Adolescence is a crucial phase in identity formation that requires optimal psychological well-being. Career decision-making is one of the key factors influencing this condition. This study aims to examine the effect of career decision-making on adolescents' psychological well-being and to investigate the role of parental involvement as a moderating variable. A quantitative approach with correlational design and Moderated Regression Analysis (MRA) was employed. Participants were 118 twelfth-grade students at MA Darul A'mal, Metro City, selected through purposive sampling. Instruments included the career decision scale, parental involvement scale, and psychological well-being scale. Results showed that: (1) career decision-making had a significant positive effect on psychological well-being (B = 0.524; sig. = 0.000); (2) parental involvement significantly moderated the relationship between career decision-making and psychological well-being (B interaction = 1.822; sig. = 0.009); (3) simultaneously, the variables explained 53.7% of the variance in psychological well-being. These findings imply the importance of career guidance programs that integrate parental involvement to enhance adolescent psychological well-being.